The impact of financial risks to financial performance indictors based on accounting profit (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed at analyzing the impact of some types of financial risks on financial performance with its indicators based on accounting profit(return on assets, return on equity), in order to determine the size of the risks that banks are likely to be exposed, which included all banks listed on the Damascus Stock Exchange., and relied on the descriptive, analytical and standard approach for the time period extending from 2010 to 2020, and the researcher concluded To a set of results, the most important of which are the following: That there is an effect of credit risk on the financial performance with its indicators (return on assets, return on equity), and there is also an effect of interest rate risk on financial performance with the return on assets index only, while there is no effect of interest rate risk on financial performance with the return on equity index Therefore, the researcher presented a set of recommendations, the most important of which are: Giving greater importance to analyzing financial risks because of its impact on financial performance based on the results of the study, as well as increasing focus on studying the impact of factors and variables that are likely to affect financial performance that are not studied in the research, due to its importance to the survival and continuation of the work of banks.